EFFORTS TO IMPROVE NURSING COMMUNICATION: A NARRATIVE REVIEW - Ariefatun Nisa Nisa; Luky Dwiantoro; Bambang Edi Warsito (Nurse and Health: Jurnal Keperawatan, 2021)
Background: Communication is an interaction process that is highly essential in building nurse-patient interpersonal relationships. Good nurse communication-patient will have a good impact on the treatment plan and recovery for the patient. Improper communication can lead to mistaken nursing care provision and even lead to injury and death. Objective: This literature review aimed to know the efforts to improve nurse-patient communication. Design: This literature review used narrative review design. Data Sources: The databases used in narrative review are Scopus, Science Direct, ProQuest, and PubMed. The journal is limited to the publication year 2016 - 2020 with the area of ​​the nursing medicine journal, full text Portable Document Format (PDF) journal. This literature review uses 4 articles appropriate the inclusion criteria. The study of articles and data extraction were carried out separately by the researcher, if there were differences, the results were taken by consensus. Review Methods: The review method for this literature review using a narrative method by classifying the similar extracted data according to the research findings. Results: The databases used in the literature review are Science Direct, Scopus, PubMed and ProQuest. The journal is limited to the 2016 – 2020 publication year with the area of ​​nursing medicine journals, improving nurse communication, full text open access pdf journals, research designs. This literature review was identified with the number of science direct: 45, Scopus: 242, PubMed: 36 and ProQuest: 492, then screened and found 4 articles that matched the inclusion criteria. The study of articles and data extraction were carried out separately by the researcher, if there were differences, the results were taken by consensus. Conclusion: Nurse communication training has a positive impact where nurses have skills in developing knowledge and capability in improving nurse communication performance. Good communication nurse-patient can increase the patient's cure rate.